Retraction Note: “4.4 First record of the goblin shark Mitsukurina owstoni Jordan, 1898 (Lamniformes: Mitsukurinidae) in the Mediterranean Sea” by Athanasios Anastasiadis, Evangelos Papadimitriou and Frithjof C. Küpper in: Kousteni, V. et al. (2022). New records of rare species in the Mediterranean Sea (May 2022). Mediterranean Marine Science, 23 (3), 417-446, doi: 10.12681/mms.28372 and Reply to Comment on “First record of the goblin shark Mitsukurina owstoni Jordan, 1898 (Lamniformes: Mitsukurinidae) in the Mediterranean Sea” by Jürgen Pollerspöck, Simon Weigmann, Bernard Seret and Nicolas Straube. Mediterranean Marine Science, 24 (1), 101-103, doi: http://doi.org/10.12681/mms.32478 - ANASTASIADIS, ATHANASIOS; PAPADIMITRIOU, EVANGELOS; KÜPPER, FRITHJOF C. (Mediterranean Marine Science, 2023)
The above authors remove these recent publications due to remaining uncertainty because they are based on a visual observation by a citizen (citizen science), without a specimen being available. The available information was not adequate to support this record based solely on photographic evidence and direct contact between the authors and the citizen.